Molecular structure of calcium, magnesium, strontium and barium m-nitrobenzoates. Issue 3 (2010) - Samsonowicz Samsonowicz, Mariola Mariola
Abstract : The effect of calcium, magnesium, strontium and barium ions on the electronic structure of m-nitrobenzoates was studied. The FT-IR spectra of m-nitrobenzoic acid and its salts were registered, assigned and analyzed. Characteristic shifts and changes in intensities of bands along the metal series were observed. The structures of m-nitrobenzoic acid and its calcium, magnesium, strontium and barium salts were optimized at the B3LYP/LANL2DZ level. Geometric aromaticity indices, atomic charges, dipole moments and energies were also calculated.